2013
DOI: 10.3233/jbr-130050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential of gamma radiation as a conservation treatment for blackberry fruits

Abstract: BACKGROUND: Blackberries consumption has been associated with health benefits. However, these fruits present a short shelflife. Thus, food irradiation is a potential alternative technology for conservation of these fruits without use of chemicals. OBJECTIVE: Analyse the potentiality of gamma radiation as a decontamination method for blackberry fruits. METHODS: Fresh packed blackberries were irradiated in a Co-60 source at two doses (1.0 and 1.5 kGy). Bioburden, physical and rheological, sensorial and total sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…These counts also increased in the irradiated fruits samples but numbers were far below than that of the nonirradiated fruit sample. An increase of the number of microbial loads in 1.0 kGy irradiated fruits of blackberries were also described by Oliveira et al (2013). However, it is noteworthy to mention that microbial counts of irradiated samples increased in a slow rate than that of non-irradiated sample during storage.…”
Section: Resultsmentioning
confidence: 71%
“…These counts also increased in the irradiated fruits samples but numbers were far below than that of the nonirradiated fruit sample. An increase of the number of microbial loads in 1.0 kGy irradiated fruits of blackberries were also described by Oliveira et al (2013). However, it is noteworthy to mention that microbial counts of irradiated samples increased in a slow rate than that of non-irradiated sample during storage.…”
Section: Resultsmentioning
confidence: 71%
“…Similarly, Oliveira et al. (2013a) have reported that 1.5 kGy gamma radiations reduced loss of fruit firmness for 2 days as opposed to control in “Primark” blackberry fruit. Sensory attributes related to phytochemical levels in harvested fruit are dependent upon the type of material used for producing gamma irradiations.…”
Section: Postharvest Quality Management Of Rubus Berriesmentioning
confidence: 82%
“…The results showed that radiation had no significant effect on the healthy fruit rate within 7 days. This was consistent with previous studies that irradiation doses up to 1.5 kGy did not result in a major impact on physical and sensory attributes (Oliveira et al ., 2013). After 7 days, the radiated blueberry fruit decayed slower than the blueberry fruit without radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Low‐medium dose radiation (<5 kGy) was reported to inhibit fruit decay, delay senescence and prolong the storage period by inhibiting membrane lipid peroxidation and respiratory metabolism (Wang & Meng, 2016; Wang et al ., 2017b; Li et al ., 2021; Liu et al ., 2023). A few studies have reported that irradiation at a low‐dose level (up to 3 kGy) had no significant impact on the physical and sensory attributes of blueberry within a short period of storage (Oliveira et al ., 2013; Golding et al ., 2014). Fruit chemical constituents that contribute to flavour quality include sugars, acids and aroma volatiles.…”
Section: Introductionmentioning
confidence: 99%